1991
DOI: 10.1002/rcm.1290050415
|View full text |Cite
|
Sign up to set email alerts
|

Conformational changes in proteins probed by hydrogen‐exchange electrospray‐ionization mass spectrometry

Abstract: Hydrogen-exchange electrospray-ionization mass spectrometry is demonstrated to be an effective new method for probing conformational changes of proteins in solutions. The method is based on the mass spectrometric measurement of the extent of hydrogen/deuterium exchange that occurs in different protein conformers over defined periods of time. Results are presented in which hydrogen-exchange electrospray-ionization mass spectrometry is used to probe conformational changes in bovine ubiquitin induced by the addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
333
0
3

Year Published

1994
1994
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(346 citation statements)
references
References 17 publications
(6 reference statements)
10
333
0
3
Order By: Relevance
“…Currently, we have no definitive explanation for this charge-shifting behavior. Denaturation has been shown to lead to higher charging (Katta & Chait, 1991aLeBlanc et al, 1991;Loo et al, 1991Loo et al, , 1993a. However, we consider the possibility of further denaturation to be unlikely under these conditions because the myoglobin should already be completely denatured in a 4% acetic acid/50% acetonitrile solution and this same effect is also observed with peptides as small as 6 residues, which are unlikely to have higher-order structure (data not shown).…”
mentioning
confidence: 88%
“…Currently, we have no definitive explanation for this charge-shifting behavior. Denaturation has been shown to lead to higher charging (Katta & Chait, 1991aLeBlanc et al, 1991;Loo et al, 1991Loo et al, , 1993a. However, we consider the possibility of further denaturation to be unlikely under these conditions because the myoglobin should already be completely denatured in a 4% acetic acid/50% acetonitrile solution and this same effect is also observed with peptides as small as 6 residues, which are unlikely to have higher-order structure (data not shown).…”
mentioning
confidence: 88%
“…H /D exchange (HDX) is one of the most popular techniques for the structural elucidation of biomolecules in mass spectrometry and has been widely implemented for both solution [1][2][3][4] and gas phase studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In solution, the extent of HDX can be directly related to the solvent accessibility of amino acid residues in proteins.…”
mentioning
confidence: 99%
“…Beauchamp and coworkers [9] suggested that lower basicity reagents, such as D 2 O and CH 3 OD, proceed via a "relay" mechanism [20] for protonated peptides, while the higher basicity ND 3 reagent gives rise to an "onium" mechanism [21]. In the case of amino acids cationized by an alkali metal ion rather than a proton, polar deuterating ligands such as D 2 O can exchange via a similar relay mechanism involving charge solvation-zwitterion (CS-ZW) isomerization [18]. Modeling of observed HDX processes and quantum chemical calculations of the potential surfaces have made a strong circumstantial case that ZW structures are traversed in many cases during HDX with basic partners like D 2 O, CH 3 OD, and ND 3 [14,16,18].…”
mentioning
confidence: 99%
“…(J Am Soc Mass Spectrom 2007, 18, 1525-1532) © 2007 American Society for Mass Spectrometry E lectrospray ionization mass spectrometry (ESI-MS) has emerged as a powerful tool to investigate the conformation, dynamics, and interactions of proteins (recently reviewed in [1][2][3][4][5]). ESI-MS has been used to probe protein conformation in solution either by measuring mass changes in response to hydrogendeuterium exchange, or by monitoring the charge state distribution (CSD) of protein ions in the gas-phase [6,7]. Advantages of ESI-MS as a conformational probe include the preservation of native conformation and noncovalent protein-protein interactions, as well as its sensitivity and speed of analysis, applicability to large proteins, and compatibility with rapid mixing approaches to examine kinetic events [3].…”
mentioning
confidence: 99%